Nilai Kearifan Lokal Dalam Memperingati Tradisi 1 Suro Nyai Ageng Ngerang Tambakromo Pati - Mifta Diana Rizki; Destiana Putri; Anisa Apriliani; Arinda Indiwara; Mohammad Kanzunnudin (Jurnal Budaya Nusantara, 2023)
The purpose of this study was to analyze the value of local wisdom in commemorating the tradition of 1 suro nyai Ageng Ngerang Tambakromo Pati. This study used a qualitative approach with a descriptive approach. The data sources used were data sources in research, namely interviews, observations and documentation. The conclusion of this study is that Nyai Ageng Ngerang is a woman of Majapahit descent. He is a migrant as well as a pedestal breaker in the Ngerang area. According to the explanation from the caretaker, Nyai Ageng Ngerang was not willing to know his real name, even now no one knows the year of birth of Nyai Ageng Ngerang. It is said that the first time he found Nyai Ageng Ngerang's grave was Mbah Gowa who was also the caretaker of Nyai Ageng Ngerang's grave. Meanwhile, to commemorate the haul of Nyai Ageng Ngerang, it is held once every year, which coincides with 1 Suro. There are a lot of series of events when commemorating the haul of Nyai Ageng Ngerang. From this series of events, local wisdom values ​​can be taken. In commemoration of Nyai Ageng Ngerang's funeral, of course, there were special invited guests who were brought in directly from the Solo Palace to take part in Nyai Ageng Ngerang's funeral. Usually those who are sent to come to the Suronan Nyai Ageng Ngerang event are representatives of the sons and daughters of Ragil from the Solo Palace.